DOI: 10.11606/d.6.2016.tde-07112016-141429
|View full text |Cite
|
Sign up to set email alerts
|

O desafio do direito à autonomia: uma experiência de Plano de Parto no SUS

Abstract: AGRADECIMENTOSAgradeço às mulheres que entrevistei pela confiança de compartilharem suas histórias e pelas esperanças renovadas a partir de seus depoimentos.À Patrícia, professora preceptora da EACH/USP, por ter me recebido com tanto entusiasmo em seu território de ensino e aprendizagem .Ao Dr. Alberto Aguemi pelas parcerias e pela ajuda em abrir as portas da SMS/São Paulo para essa pesquisa.Às/Aos colegas do Grupo de Pesquisa GEMAS pelos bons momentos de convivência, discussões e aprendizados.Ao guruji B.K.S.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
8

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 7 publications
(8 reference statements)
0
11
0
8
Order By: Relevance
“…In this respect, De Jonge et al 52 indicate that women with higher levels of schooling are more likely to give birth in nonrecumbent positions, while a systematic literature review of abuse and disrespect during birth care conducted by Bohren et al 34 reported that less informed women and those with lower levels of schooling receive poorer quality care. It is therefore vital to strengthen actions directed at providing women with clear and adequate information about what to expect in the maternity facility and encouraging the elaboration of care plans 47 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, De Jonge et al 52 indicate that women with higher levels of schooling are more likely to give birth in nonrecumbent positions, while a systematic literature review of abuse and disrespect during birth care conducted by Bohren et al 34 reported that less informed women and those with lower levels of schooling receive poorer quality care. It is therefore vital to strengthen actions directed at providing women with clear and adequate information about what to expect in the maternity facility and encouraging the elaboration of care plans 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Another factor associated with variation of practices were the characteristics of birthing women. Women called "IP" (jargon for "informed patient") are those who seek information through their social relations or social media, such as the blogosfera materna (maternal blogosphere) [44][45][46] , which encourages the active participation of women in decision making about the birth and the elaboration of the birth plan 47 :…”
Section: What Facilitates and Hinders Flexibility When It Comes To Bimentioning
confidence: 99%
“…Thus, obstetrics currently perpetuates the medical preference for surgical delivery as a prophylactic measure that protects women from the intrinsic risks and the doctor from uncertain outcomes related to vaginal delivery 32 . The higher numbers of interventions to shorten delivery time are seen by courts in a more positive light than vaginal delivery 33 .…”
Section: Individual Dimension: Actionmentioning
confidence: 99%
“…Apenas a IHAMC se preocupa com a presença de políticas não discriminatórias, ressaltando a importância de olhar para grupos de mulheres HIV-positivas, para adolescentes e minorias étnicas, entre outros. No Brasil, entre outras iniciativas, a Política Nacional de DST/Aids inclui em suas estratégias a prevenção e o controle da sífilis congênita e a redução da transmissão vertical e a portaria relativa à organização da atenção à gestação de alto risco prevê que o serviço de pré-natal faça o encaminhamento da gestante portadora de HIV/Aids a um centro de referência (MINISTÉRIO DA SAÚDE, 1999, 2016. A cobertura da testagem é maior que 80% e a prevalência da infecção por HIV é menor que 1% entre as gestantes no país, todavia, há iniquidades no acesso aos serviços de saúde (DOMINGUES et al, 2015).…”
Section: Cuidado Amigo Da Mulher Da Ihac Mother-friendly Childbirth Iunclassified
“…A paciente bem informada (chamada de "PI"), que entende a fisiologia do parto e conhece os seus direitos, de certa forma desestabiliza o serviço e o obriga a uma rápida reorganização, com a prestação de um atendimento mais cuidadoso a essa mulher. Nesse sentido, pode ser valioso convidar as gestantes para pensar em seu plano de parto, entendendo-o como um instrumento para a negociação do cuidado com a equipe da maternidade (MÜLLER et al, 2012;ANDREZZO, 2016). Igualmente importante é constituir estratégias para sensibilização das mulheres sobre seus direitos sexuais e reprodutivos, principalmente no atual contexto político, em que se tende restringir os direitos das mulheres.…”
Section: Considerações Finaisunclassified